1999
DOI: 10.1557/proc-602-177
|View full text |Cite
|
Sign up to set email alerts
|

Charge Inhomogeneities in the Colossal Magnetoresistant Manganites From the Local Atomic Structure

Abstract: We have measured atomic pair distribution functions (PDF) of La 1,x Ca x MnO 3 using high energy x-ray diffraction. This approach yields accurate PDFs with very high real-space resolution. It also avoids potential pitfalls from the more usual neutron measurements that magnetic scattering is present in the measurement, that the neutron scattering length of manganese is negative leading to partial cancellation of PDF peaks, and that inelasticity effects might distort the resulting PDF. We have used this to addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Similar conclusions as those found by Billinge et al (1996Billinge et al ( , 1999 were reached by Booth et al (1998aBooth et al ( , 1998b) using x-ray absorption measurements applied to La 1−x Ca x MnO 3 at several hole concentrations. This technique provides information about the distribution of Mn-Mn bond lengths and the Mn-O environment.…”
Section: X-ray Absorption Transport and Magnetismsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar conclusions as those found by Billinge et al (1996Billinge et al ( , 1999 were reached by Booth et al (1998aBooth et al ( , 1998b) using x-ray absorption measurements applied to La 1−x Ca x MnO 3 at several hole concentrations. This technique provides information about the distribution of Mn-Mn bond lengths and the Mn-O environment.…”
Section: X-ray Absorption Transport and Magnetismsupporting
confidence: 87%
“…Whether the distorted octahedra are randomly distributed, compatible with the polaronic theory, or gathered into larger structures, compatible with the phase separation theory, has not been analyzed. More recent studies by Billinge et al (1999), using the same technique, produced the schematic phase diagram shown in Fig.IV.a.5. Note the light shaded region inside the FM phase: in this regime Billinge et al (1999) believe that localized and delocalized phases coexist.…”
Section: Pdf Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach will result in short, medium and long range structural information, depending on the refinement range r max . The PDF approach has been used extensively to study the local structure of other manganites 13,14,15,16,17 and a great overview of the technique applied to a variety of complex materials can be found here. 18…”
Section: Introductionmentioning
confidence: 99%
“…Magnetoresistive materials are those that have an electrical conductivity that varies depending on the applied magnetic field; the term ''colossal'' distinguishes those materials which display the effect to an abnormally large extent-greater even than the so-called ''giant'' magnetoresistors. The end members 76,77 and other compositions in the series [78][79][80][81] have been studied using PDF measurements, with the primary emphasis placed on how the structure changes as a function of temperature and/or composition. The average structure is largely unaffected by each of the various electronic/ orbital transitions implicated in CMR behaviour, but it was shown that the electronic phase diagram was actually replicated by local correlations extracted from the PDF data [ Fig.…”
Section: Jahn-teller Active Materialsmentioning
confidence: 99%